Employee Diklat on Employee Data Application System PT. Indonesian Port I (Persero) - Muhammad Amin (Jurnal Mantik, 2020)
Technology and information that are increasingly developing and increasingly sophisticated must be balanced according to our needs. Due to the increasing complexity of the work that we do, it cannot be denied that every agency or other institution is in dire need of technology, which can simplify and speed up work. One of them we can use computer technology, especially computers that use desktop software. So far, education and training staff if there are employees and prospective employees who want to take part in education and training, the data only exists on paper which contains employee and prospective employee data forms, so that data regarding education and training transactions, costs and employee data is not easily stored, if the staff education and training wants to recap the data, it is necessary to check the data archive of employees and prospective employees one by one. Therefore, the authors try to design an information system that can later help Pelindo employees, especially the education and training section. Based on the results of these studies, the authors make a Data Training Application System at PT. Pelabuhan Indonesia I (Persero).